Aspartate aminotransferase-platelet ratio index and body mass index in children with fatty liver - Ninung Kusumawati; Maria Mexitalia; Suci Romadhona (Indonesian Pediatric Society, 2012)
Background Obesity in children is becoming a global epidemic.Nonô€€·alcoholic fatty liver disease (NAFLD) is a highly prevalentand potentially serious complication of childhood obesity. Theearly identification of fibrosis is important in children v.ith NAFLDin order to prevent the development of liver disease in adulthood.One nonô€€·invasive procedure to predict liver fibrosis is the aspartateaminotransferase (AST)ô€€·platelet ratio index (APRI).Objective The purpose of our study was to assess a correlationbetween APRI and body mass index (BMI) in obese childrenwith fatty liver.Methods A crossô€€·sectional study was conducted from August toSeptember 2007. Subjects were obese children from one juniorhigh school in Semarang. Complete blood count, transaminaseenzyme measurement, and abdominal ultrasound (USG) wereperformed on each subject. Only subjects with bright liver onUSG underwent APRI analysis. Spearman's correlation was usedfor statistical analysis.Results Of 3 7 obese children, 19 children had bright liver on USG.Their mean APRI was 0.16 (SD 0.119). Only one obese subject(1137) with bright liver had an APRI > 0.5. APRI was significantlycorrelated to alanine amino transferase (ALT) levels (r = 0.62),but not significantly correlated to weight and BMI.Conclusion There was no correlation between APRI and BMI.Only lout of 37 obese children with fatty liver had APRI levelsindicating the presence of liver fibrosis. [Paediatr Indones.2012;52:181-4].